PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT GUNA MENINGKATKAN KUALITAS PELAYANAN JASA PADA KOPERASI AGRONIAGA INDONESIA SYARI’AH - Ahmad Yani (Universitas muhammadiyah malang, 2013)
AhmadYaniPT. Visiland Dharma Sarana Jakarta PusatE-mail: yani.06djava@gmail.comABSTRACTThe research objective was to implement QFD (Quality Function Deployment) to improve the qualityof service on Kanindo Shari’ah. Variables consisted of direct evidence, reliability, responsiveness,assurance, empathy. Phase of the QFD were (1) poll (Voice of Customer), (2) analysis with QFD, (3)the preparation of Quality Houses. Respondents were customers on Kanindo Shari’ah, namely 40customers who were collected by using accidental sampling. The results showed that the improvementin the quality of services performed by observing attributes of interest to the customer. Then, thecustomer satisfaction performance attributes were the most satisfying hospitality and good communication.Competitive satisfaction performance attributes satisfied customer was adequate infrastructure.Goal was the most preferred attribute settle by Kanindo Shari’ah. The highest value on ImprovementRatio was the speed, precision and accuracy of serving customers. Sales point showed a stronglevel of sales. Finally, the analysis of the results obtained planning quality improvement services inthe form of House Of Quality (HOQ)Keywords: Quality function deployment, direct evidence, reliability, responsiveness, assurance, empathy,house of quality